Some Meat Characteristics in Karya Lambs - YaralÃ„Â±, E; Karaca, O (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2013)
A research was conducted during 2008 and 2009 to determine meat quality characteristics in 72 male and female Karya lambs in pasture, pasture plus feeding and intensive conditions. Significant differences were obtained between fattening groups in M. Longissimus Dorsi muscle for L* (lightness) and the highest value was calculated in intensive groups and male lambs. Also the meat colour appeared redder (high a* value) in this group and their male lambs. The intermusculer fat (marbling) was evaluated better in intensive group and male lambs. Regarding fatty acid composition, while SFA and MUFA were increased in intensive conditon, C16:0 was the highest, C18:0 and C18:1 n-9 were the lowest value in pasture lambs. Ä°t is concluded that the pasture feeding increased P/S, CLA and n-6 PUFA/n-3 PUFA values.Animal Production 15(2):127-134, May 2013